A Passiva em português como construção predicativa adjetival: evidência morfológica e implementação computacional em LFG/XLE (Passive as adjective predicative construction in portuguese: morphological evidence and implementation in LFG/XLE) - Alencar, Leonel Figueiredo de (Estudos da Língua(gem), 2015)
Gramáticas tradicionais do português tratam a passiva como voz, incluindo-a no quadro da conjugação verbal. Neste artigo, discutimos os argumentos de Perini (2010) de que não há voz passiva em português e relacionamos essa proposta com a abordagem da POLFIE, uma gramática do polonês desenvolvida no quadro da LFG e implementada no sistema XLE. Conforme essa gramática, a passiva é uma construção predicativa adjetival. Apresentamos uma evidência adicional, de natureza morfológica, do estatuto adjetival do particípio passivo em português e implementamos essa análise na BrGram, uma gramática do português do Brasil nos moldes da POLFIE. PALAVRAS-CHAVE: Voz Passiva. Gramática Léxico- Funcional. Linguística Computacional. Parsing Sintático. Sufixos Avaliativos. ABSTRACT Traditional grammars of Portuguese handle the passive construction as a voice phenomenon which is part of the verbal conjugation. In this paper, we discuss the claim by Perini (2010) that there is no passive voice in Portuguese. We compare this approach to the one of POLFIE. This is a computational grammar of Polish which was developed within the framework of LFG and implemented in XLE. In this grammar, the passive construction is an adjective predicative construction. We present additional morphological evidence on the adjectival status of the passive participle in Portuguese and implement this analysis in BrGram, a computational grammar of Brazilian Portuguese that is analogous to POLFIE. KEYWORDS: Passive Voice. Lexical-Functional Grammar. Computational Linguistics. Syntactic Parsing. Evaluative Suffixes.